Membangun Impian di Tepi Sungai: Strategi Pengelolaan Taman Bacaan Ransel Buku dalam Keterbatasan - Endah Yusma Pratiwi; Hendrowanto Nibel; Syarah Veniaty; Yesninopy Yesninopy; Priska Lestari Siregar; Murnihati Harefa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study is to determine the management strategy of the Backpack Book Reading Park by first looking at its limitations. This research method uses a qualitative research approach. The selection of informants uses a purposive sampling technique. The results of the study showed that in Ransel Buku there were limited human resources which included the busyness of the managers and the lack of volunteers from outside. Management strategies included arranging books in rows, upgrading reading materials, opening dance classes, involving learners to participate outside Ransel Buku, involving parents/community in activities, maintaining good relations with donors and volunteers, and involving teachers to attend workshops. The conclusion is that these limitations do not make Backpack Book's performance decline, but with various strategies, efforts are still made so that students, especially children, enjoy studying at Backpack Book. Each reading park has its own strategy that adapts to the situation and conditions. Keywords: Community Reading Park (TBM), Management, Ransel Buku, Strategy.